PERBANDINGAN PENDIDIKAN ISLAM: (Peretas Tradisi-Akut Pendidikan Islam) - Hj. Djuwairiyah Djuwairiyah; Abd. Muqit (LP2M Universitas Ibrahimy, 2017)
Education is inevitability in life. For reaching even life perfect must be traversed by education because all side of human life is not loose from education. Feel of strong crusty push some people for knowing and studying about real life in community environment and country so that causing mutual understanding, cooperation and hel each other for achieving goals to progress together. For that required comparative study. According to Carter V. Good about Comparative education is a study in charge of comparison of theory and practice in countries which have mean for broadening views and knowledge beyond limit of his country. Method and approach of comparative study are use such as Islamic education. To advance some education must be comparative to other countries for knowing equation and difference, advantages and deficiency. So that we can take some of positive unsure which adjusted by local condition.